2012
DOI: 10.1002/jcp.23027
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors induce mitochondrial elongation

Abstract: Although various stimuli-inducing cell demise are known to alter mitochondrial morphology, it is currently debated whether alteration of mitochondrial morphology is per se responsible for apoptosis execution or prevention. This study was undertaken to examine the effect of histone deacetylase (HDAC) inhibitors on mitochondrial fusion-fission equilibrium. The mechanism underlying HDAC inhibitor-induced alteration of mitochondrial morphology was examined in various cells including primary cultured cells and untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…However, some studies showed that apoptosis-inducing agents could result in mitochondrial elongation. A previous study reported that HDAC inhibitors, which induce apoptosis, caused mitochondrial elongation in various cells in addition to inducing apoptosis (24). Our data suggest that G-TPP induces mitochondrial elongation by reducing and inactivating the mitochondrial fission-regulating protein Drp1 and increasing the ROS level.…”
Section: Discussionsupporting
confidence: 56%
“…However, some studies showed that apoptosis-inducing agents could result in mitochondrial elongation. A previous study reported that HDAC inhibitors, which induce apoptosis, caused mitochondrial elongation in various cells in addition to inducing apoptosis (24). Our data suggest that G-TPP induces mitochondrial elongation by reducing and inactivating the mitochondrial fission-regulating protein Drp1 and increasing the ROS level.…”
Section: Discussionsupporting
confidence: 56%
“… 76 Histone deacetylase inhibitors have previously been reported to promote mitochondrial fusion, which can be abolished by either OPA1 or Mfn1 downregulation. 78 , 79 Thus, we could not totally exclude the possibility that histone deacetylase inhibitors played a role in modulating Stat3 acetylation levels in our study; nevertheless, our data strongly supported the idea that Stat3 acetylation and RelA play key roles in upregulating OPA1 expression and thus improving mitochondrial dynamics.…”
Section: Discussionmentioning
confidence: 54%
“…It is also worth noting that HDAC inhibitors have been shown to increase mitochondrial fusion under non-stressed conditions. However, this activity is independent of HDAC6 and involves down-modulation of DRP1 (Lee et al, 2012;Tailor et al, 2013).…”
Section: Discussionmentioning
confidence: 99%